SUCCESSION OF SHARES IN A POLISH LIMITED LIABILITY COMPANY: A COMPARATIVE PERSPECTIVE - Boś , Kacper (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2025)
This paper aims to conduct a analysis of the process of succession of shares in Polish limited liability company (spółka z ograniczoną odpowiedzialnością) from a comparative perspective. The comparative study is based on German and US regulations concerning the companies which in their characteristics most closely resemble Polish limited liability company. Under German law it is the Gesellschaft mit beschränkter Haftung, whereas under US law – the Limited Liability Company, regulated by the Revised Uniform Limited Liability Company Act, which has been adopted in numerous US states. The analysis in this paper leads to a conclusion that the solutions concerning the succession of shares in limited liability company applied in the Polish legal system seem to lie between the German and American regulations. Unfortunately, Polish regulation ultimately also proves to be incomplete due to a very laconic formulation of art. 183 of Polish Commercial Companies Code, which leads to many considerable legal issues. One of the most significant of these is issues it the legal nature of the sp. z o.o.-share, which in the doctrine and the judiciary is considered a ‘relatively heritable right’. The comparative analysis conducted in this paper suggest that it would be desirable to change the Polish regulation and opt for the mandatory inheritance of shares, as it is in German law.